A velhice e a produção contemporânea de subjetividades: experiências universitárias e educação aberta - Doronin, Juliana de Aquino Fonseca (2021)
Contemporary age can be perceived by the multiple subjectivations of power, such as: old age as human capital manufactured by the market; old age as a subject of rights, linked to the dimension systematized by a “plastered and standardized” legal statute, which does not consider the singularities of this subject of rights; and old age as aesthetics of existence, linked to the production of subjectivity in the “artist of life”, with a desire for power, increased positively or negatively to the conduct of his life, regardless of his chronological age. An empirical research was carried out from September 2016 to November 2018, with elderly participants of the groups in two Higher Education Institutions, Universidade Aberta a Terceira Idade (UNATI) of the State University of Maringá (UEM) and the extension project “Viver Melhor ”From the State University of Paraná (UNESPAR), both with a focus on citizenship. Documentary research, observation and twenty meetings were carried out with and some relatives of the elderly, with the aim of realizing the impact that these experiences brought to their lives in what way they are conducted in practice. The use of poetry in this study demonstrates a “new tool” to do science, following three movements of thought based on the “how”: has old age been introduced into the debate on public and educational policies? How does this policy fit into a management policy in the conduct government? and how are policies adopted in ways of life experiences (of modifications)? The initial hypothesis was that as the HEI made it possible to stimulate and promote old age and are aware of their role as citizens, acting in the development of practices strengthened by public policies existing in the Brazilian State. However, this criticism is known to be limited in actions, without questioning and advancing in the field of new proposals based on the needs of individuals and their current needs, considering societal transformations. The multiple perceptions brought up in the participants' narratives demonstrated a conception of life policy, through being bifurcated, opposite and complementary - singular and multiple at the same time. After the analysis, we believe that there are no ready and finished convictions that respond objectively to the initial concern, because we are bifurcated beings and in constant movement of experimentation, driven by impulses of subjectivity, it is still necessary to advance, given the complexity of the research and its various forms of experiments and mainly the conception that old people are subject to “plastered” public policies, however, as singularities of existence they provoke in some the power of perception that, even obtained through the mechanisms of biopolitics control-, use politics of life as a coping strategy, through the recreation of the moment